RISK MANAGEMENT IN THE ANDIR RETENTION BASIN PROJECT: A QUALITATIVE CASE STUDY - Feby Kartika Sari; Muhammad Sapto Nugroho, Darmawan Pontan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Mega infrastructure projects in Indonesia face a complex landscape of uncertainty, often hindered by significant non-technical risks such as land acquisition and financing issues. Systematic risk management is crucial to ensure project success. This research aims to comprehensively dissect and map the risk landscape in a case study of the Andir Retention Basin Project, which reflects these challenges. Using a qualitative case study approach, this study gathered primary data through in-depth interviews with key stakeholders. Through participatory discussions, each risk was identified and assessed based on its probability and impact levels. The assessment results were then mapped onto a risk matrix to determine priority levels and formulate appropriate response strategies. The research identified 12 main risks, with five categorized as Very High: Land Acquisition, Project Financing, Regulatory Changes, Bad Weather, and Work Accidents. The main conclusion of this study is that the project's risk profile is dominated by non-technical and external factors. This finding confirms that the success of modern infrastructure projects depends not only on technical excellence but also on the management's ability to proactively navigate social, financial, and regulatory complexities